The Optimization of Home Yard Utilization for Strengthening Household Economy Through the Mini Garden Program in Ralleanak Utara Village, Aralle District, Mamasa Regency: English - Supriadi, Supriadi; Yusuf, Andi Muhammad Ridho (Mattawang: Jurnal Pengabdian Masyarakat, 2025)
This community service program aims to optimize the utilization of home yards to enhance food security and strengthen household economy in Ralleanak Utara Village, Aralle District, Mamasa Regency. The program was implemented through a participatory approach involving socialization, technical training, mentoring, and monitoring–evaluation. Underutilized yards were transformed into mini gardens producing vegetables and household food crops. The results indicate improved cultivation skills, increased availability of nutritious household food, and additional income from surplus sales. On average, households harvested 5–7 kg of vegetables weekly, with 40 mini gardens established during the program. Beyond economic benefits, the initiative fostered community solidarity, reduced organic waste through compost use, and created greener environments. The success of this program demonstrates that collective utilization of home yards can promote food self-sufficiency, support sustainable livelihoods, and provide a scalable model for rural development.